Proceedings of the 9th International Conference on Cognitive Radio Oriented Wireless Networks 2014
DOI: 10.4108/icst.crowncom.2014.255708
|View full text |Cite
|
Sign up to set email alerts
|

FBMC-based air interface for 5G Mobile: Challenges and proposed solutions

Abstract: Scenarios envisaged for mobile communication systems beyond 2020 imply that future applications and services will impose highly diverse requirements on the system design. To appropriately respond to these requirements while ensuring an efficient usage of available spectrum and system resources, the air interface of 5G system is expected to provide much more flexibility compared to today's systems. Filterbank based multicarrier (FBMC) may be considered a potential enabler for that purpose, as it provides excell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
54
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(56 citation statements)
references
References 20 publications
0
54
0
2
Order By: Relevance
“…Apart from its main advantage of significantly reduced out-ofband emission in comparison to the widely used orthogonal frequency division multiplexing (OFDM) system [1], [2], [6]; another major benefit is ease in the implementation of multi-user (MU) access in the uplink transmission since the strict synchronization requirements for OFDM systems can be relaxed in FBMC systems [7], [8]. In addition, it has been reported in [9] that FBMC system is more robust to carrier frequency offset (CFO) [10], which is critical for this waveform when employed in high mobility environments and multi-cell cooperation scenarios [7], [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from its main advantage of significantly reduced out-ofband emission in comparison to the widely used orthogonal frequency division multiplexing (OFDM) system [1], [2], [6]; another major benefit is ease in the implementation of multi-user (MU) access in the uplink transmission since the strict synchronization requirements for OFDM systems can be relaxed in FBMC systems [7], [8]. In addition, it has been reported in [9] that FBMC system is more robust to carrier frequency offset (CFO) [10], which is critical for this waveform when employed in high mobility environments and multi-cell cooperation scenarios [7], [11].…”
Section: Introductionmentioning
confidence: 99%
“…However, it has been reported that a well designed prototype filter with moderate length (e.g. overlapping factor K = 4 ∼ 6) incurs negligible self-interference 1 [1], [6]. There have been some investigations in the literature on the dispersive channel induced interference in the form of ICI and/or ISI for FBMC systems.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the large side lobes exhibited by the transmit signal make OFDM unsuitable when strict synchronization cannot be attained. The filter bank multicarrier modulation based on OQAM (FBMC/OQAM) is considered as an eligible candidate to substitute OFDM and become the air-interface of 5G networks [1]. The beauty of FBMC/OQAM is that subcarrier signals can be shaped with pulses that exhibit good time-frequency localization properties, while maximum bandwidth efficiency is achieved [2].…”
Section: Introductionmentioning
confidence: 99%
“…This has become the main obstacle to integrate FBMC/OQAM with multiple-inputmultiple-output (MIMO) communication systems [1]. The orthogonality issue is overcome by introducing the CP together with the adoption of the circular filtering [3], yet this entails wasting energy and losing spectral efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Thus Staggered MultiTone (SMT) schemes like FBMC-OQAM, which utilize a critically sampled lattice grid [5], have been proposed for future wireless communication systems, e.g. 5th Generation (5G) cellular radio [6], [7]. In contrast to CP-OFDM, FBMC-OQAM allows the usage of arbitrary pulse shapes, which enables optimal adaptation of a transmission system to the actual channel conditions, thus preserving the maximum available channel capacity.…”
mentioning
confidence: 99%